The impact of cell phone addiction on adolescent hobbies – A field study on a sample of Young Saudis – - Hamzah, Rasil Abubakar; Qutub, Afnan Abdullah (Journal of Humanities & Social Sciences, 2020)
The overuse of mobile phones by teenagers has become a common occurrence in our time. Therefore, this research aims to study the impact of cell phone addiction, cell phone cons, and the effect of applications on adolescent behaviors. This survey used the questionnaire to gather information from participants. The study targeted a group of male and female school students in Jeddah in the 14- 16 age group, who numbered 270. The study found that most students spend a lot of time on these apps or one of them: (Snapchat, Instagram, Twitter, Facebook) without realizing the value of time wasted on these apps. The study also showed that Saudi teenagers use mobile phones and their applications to serve and develop hobbies. Despite the negative effects of mobile use such as sleep and insomnia, the sample praised its ability to control the use of mobile phones and that overuse does not reach the stage of addiction. The study recommends reducing the use of cell phones so that adolescents can hone and focus their skills. The study also recommends conducting qualitative studies to identify the quality of identities and how mobile devices contribute to the refinement and development of technical and technical hobbies.